Combinatorial control of adhesion of Brucella abortus 2308 to host cells by transcriptional rewiring of the trimeric autotransporter btaE gene - Sieira, Rodrigo (2016)
Regulatory network plasticity is a key attribute underlying changes in bacterial gene expression and a source of phenotypic diversity to interact with the surrounding environment. Here, we sought to study the transcriptional circuit of HutC, a regulator of both metabolic and virulence genes of the facultative intracellular pathogen Brucella. Using in silico and biochemical approaches, we identified a novel functional HutC-binding site upstream of btaE, a trimeric-autotransporter adhesin involved in the attachment of Brucella to host extracellular matrix components. Moreover, we identified two additional regulators, one of which, MdrA, acts in concert with HutC to exert a combinatorial control of both btaE promoter activity and attachment of Brucella to HeLa cells. Analysis of btaE promoter sequences of different species indicated that this HutC-binding site was generated de novo by a single point mutation in a virulent Brucella strain, indicative of a transcriptional rewiring event. In addition to major domain organization differences existing between BtaE proteins within the genus Brucella, our analyses revealed that sequences upstream of btaE display high variability probably associated to intrinsic promoter structural features, which may serve as a substrate for reciprocal selection during co-evolution between this pathogen and its mammalian host.